VEGETATION DYNAMICS AND LANDSCAPE EVOLUTION IN THE CONTACT BETWEEN CAMPINARANA AND CAMPINA ON SPODOSOLS - DEMINI RIVER BASIN-AM (BRAZIL) - Guimaraes, Felipe Silva; Bueno, Guilherme Taitson; Oliveira Mendes, Debora de Sena; Nascimento, Nadia Regina do [UNESP]; Diniz, Alisson Duarte; Souza, Jorge Batista de (Uniao Geomorfologia Brasileira, 2018)
The campinas and campinaranas are Amazonian ecosystems of great value, especially in the Rio Negro Basin. The campinaranas are an forest phytophysiognomy where C-4 metabolism plants predominate. The campinas are an grassland phytophysiognomy characterized by the abundance of C-3 plants. These ecosystems are often associated to Spodosols. These soils have a Bh horizon formed by the humus migration from the surface horizons and subsequently accumulate in some region of the profile. Studies have shown that the dynamics of contraction and expansion between campinas and campinaranas are related to pedogenetic and morphogenetic processes. The goals of this paper is to verify if there have been expansion or contraction of the campinas over the campinaranas in the study area the and propose a model to explain this dynamic. A transect was established from the edge of the low plateau toward its center so as to include the main the phytophysiognomies of the region. Along this transect pits were opened for pedological description and sample collection for physicochemical and carbon isotope ratio analysis. The latter was performed on samples of the A and Bh horizons. The interpretations made based on the available literature about the region landscape evolution, results of physical analysis and carbon isotope ratio analysis suggest the campinaranas, which are associated with Spodosols, have expanded and the campinas that lies on Gleysols and Histosols are retracting. The driving process of this dynamics is related to incision of the watercourses on the plateaus culminating in drainage and clay depletion of the plateaus.
Keywords: Carbon Isotope Ratio; Landscape Evolution; Amazonia